Comparative analysis of body weight and serum biochemistry in broilers supplemented with some selected probiotics and antibiotic growth promoters (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present work was conducted on Cobb-500 broilers fed with either probiotics (Yogurt, Promax®) or antibiotic growth promoters (Ciproflox®, Renamycin®) to assess the effects on body weight and biochemical parameters.Materials and methods: A total of 30 day-old broiler chicks were purchased and acclimatized for 7 days in the experimental shed. After initial acclimatization, the broilers were allotted into five equal groups (n=6). Group A was considered as control and was fed commercial ration and fresh drinking water. Groups B and C were fed commercial ration and probiotics (Yogurt, Promax®) respectively mixed in water. Groups D and E received commercial ration and antibiotic growth promoters (Ciproflox®, Renamycin®) respectively with water. Body weight of each bird was recorded on day 7, 14, 21, 28 and 35. At the end of trial period, the birds were sacrificed to collect blood in order to prepare serum samples for biochemical analyses considering total cholesterol, triglyceride, high density lipids (HDL), creatinine, alanine aminotransferase (ALT) and aspartate aminotransferase (AST).Results: Body weight in all treatment groups (B, C, D and E) was significantly (P